ПОРЯДОК РАБОТЫ И ХАРАКТЕРИСТИКА ПОЛНОМОЧИЙ СЕВЕРОАТЛАНТИЧЕСКОГО СОВЕТА КАК ВЫСШЕГО ОРГАНА НАТО - Tuyakbayeva, N.S. (Journal of actual problems of jurisprudence, 2019)
In article the author considers an operating procedure and the characteristic of powers of North Atlantic Council as NATO supreme organ.